Anthraquinones from Hedyotis herbacea - Permana, Dharma; Lajis, Nordin; Othman, A. Ghafar; Ali, Abdul M.; Aimi, Norio; Kitajima, Mariko; Takayama, Hiromitsu (American Chemical Society, 1999)
A new anthraquinone, 2-hydroxymethyl-10-hydroxy-1,4-anthraquinone (1), was isolated from Hedyotis herbacea along with three other known derivatives: 1,4-dihydroxy-2-hydroxymethylanthraquinone (2); 2,3-dimethoxy-9-hydroxy-1,4- anthraquinone; and 1,4-dihydroxy-2,3-dimethoxyanthraquinone. The structure of 1 was determined based on analysis of its spectroscopic data.